Réponses

2014-09-23T14:11:09+02:00
A= -4 (car l'expression donne -28/7)

B= 
(4-6)x[5+(3-(-2))x2)]
(-2)x[5+((3+2)x2)]
(-2)x(5+(5x2))
(-2)x(5+10)-2x15 = -30

C=
-7x(-3)-(-3)x(-5)
21-15 = 6
12+(-3)-2 = 9
6/9 => 2/3

Normalement c'est bon :P
2014-09-23T15:07:45+02:00
A = 7 - 7 x 5
       6 x 2- 5
A = 7 - 35
       12 - 5
A = - 28/7
A = 7 x - 4 / 7 x 1
A = - 4/1
A = - 4

B = (4 - 6) x (5 + (3 - (- 2)) x 2
B = - 2 x (5 + (3 + 2) x 2
B = 2 x (5 + 5) x 2
B = 2 x 10 x 2
B = 20 x 2
B = 40

C = - 7 x (- 3) - (- 3) x (- 5)
           12 - (- 3) - 2
C = 21 - (+ 15)
       12 + 3 - 2
C = 21 - 15
      15 - 2
C = 6/13